Nighttime exercise, sleep quality and Salah concentration of adult Muslims in Johor / Ummul Nadzirah and Mohd Suleiman Murad - Nadzirah, Ummul; Murad, Mohd Suleiman (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Exercise is a subcategory of physical activity which is structured, repetitive and purposeful. This study focuses on only one of the pillars of Islam, which is to perform the salah (prayer). Various research studies measure exercise with sleep outcome but none of the study focus on its relation to religious practice, thus how nighttime exercise affect sleep quality and its relation to religious practices of Muslim is yet to be known. A cross-sectional study using an online questionnaire was implemented to identify how nighttime exercise affect sleep quality and its relationship with religious practices among Muslim focusing on concentration in prayer or salah (fajr) which was done at the dawn by Muslims. A total of 176 Muslims young adults participated in this research. Overall, the results found that different types of night exercise intensity influence the ability of respondents to wake up early for fajr (p=0.005). In fact, poor sleep quality gives a significant impact to concentration in prayer (fajr) (p<0.05). However, poor sleep quality was not affected by different age intervals, duration and frequency, and type of night exercise intensity. Future study should focus on awareness of sleep hygiene among Muslims as in this study poor sleep quality was proven to give an impact. Moreover, future study needs to consider other reasons that contribute to their trouble sleeping despite doing nighttime exercise. For example, how religious the respondents are also can be considered as one the variables that may affect both abilities to wake up early for fajr and concentration in salah (fajr) following nighttime exercise.